Shock synthesis and characterization of titanium dioxide with α-PbO2 structure. (8th June 2018) - Tan, Zhen; Chen, Pengwan; Zhou, Qiang; Liu, Jianjun; Mei, Xiaofeng; Wang, Bi; Cui, Naifu
Abstract: The phase transformation behavior of anatase and rutile titanium dioxide with particle sizes of 60 nm and 150 nm under shock compression have been investigated. To increase the shock pressure and reduce the shock temperature, copper powder and a small amount of paraffin were mixed with the TiO2 powder. The shock recovered samples were characterized by x-ray diffraction, Raman spectroscopy, and transmission electron microscope. The results indicate that both anatase and rutile TiO2 can transform to α -PbO2 phase TiO2 through shock-induced phase transition. The transformation rate of α -PbO2 phase TiO2 for anatase TiO2 under shock compression is 100% and pure α -PbO2 phase TiO2 can be obtained, while the transformation rate for rutile TiO2 is over 90%. The influence of the particle size on the yield of α -PbO2 phase TiO2 is not noticeable. The thermal stability of the recovered pure α -PbO2 phase TiO2 was characterized by high temperature x-ray diffraction, thermogravimetric analysis and differential scanning calorimetry. The results show that α -PbO2 phase TiO2 transforms to rutile TiO2 when heated to temperature higher than 560 °C. The mechanisms of the phase transition of TiO2 under shock compression are discussed.